Relevance of bone mass, bone mineral density and bone metabolic markers in long-distance runners - Asano, S.; Torii, S.; Iida, Y.; Iizuka, S. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The osseous tissue is maintained through continuous formation and resorption. Many studies have reported that bone metabolism is altered in accordance with the type, intensity and frequency of the exercise. Recently, the usefulness of the bone metabolism markers evaluating bone turnover quantitatively attracts attention as screening tool for bone injury such as the stress fracture. How ever, few studies have analyzed the bone metabolism marker of the competitive athletes, continuously. We measured whole body bone mass, bone mineral density of the lumbar spine and bone metabolism markers in 16 male athletes belonging to a business group longdistance running team, longitudinally and cross-sectionaly. Method: We measured BAP as a bone formation marker and TRACP-5b as a bone resorption marker in serum, and whole body bone mass and bone mineral density of the lumbar using DXA (Delphi-A QDR). Result: The levels of BAP and TRACP-5b in a few subjects exceeded beyond their normal range of young male. In addition, a negative correlation tendency was seen between bone mineral density of the lumbar and product of BAP multiplied by TRACP-5b, which expressed bone metabolism states. Discussion: Uncoupling of the bone metabolism may exist in athletes performing high intensity exercise like a longdistance running continuously. These results showed that bone mineral density of the lumbar spine was low in athletes with high bone metabolic turnover, resulting in high frequency of stress fracture. We suggested that bone metabolism markers are useful from a point of view assessing bone states of athletes and preventing their bone injury.